Hernández Huerta, J. L., Quintano Nieto, J. y Ortega Gaite, S. (2014). Educación y Utopía. Ensayos y Estudios. Salamanca: FahrenHouse; 257 pp. ISBN 978-84-942675-3-6 - Azrak, Adrián (Journal of Supranational Policies of Education (JOSPOE), 2016)
Journal of Supranational Policies of Education (JoSPoE)